The Relationship Between Body Size and Bone Weight (Breast and Thigh) in Kampung Chicken (Gallusdomesticus) Results Third Generation Selection - Liza Wati; Helmi Ediyanto; Eko Wiyanto; Depison Depison (Buletin Peternakan, 2023)
The aim of this study is to identify the characteristics of body size and shape in kampung chickens, as well as the relationship between body size and meat weight. To achieve this, 200 kampung chicken DOC were directly observed using purposive sampling. Purposive sampling where the chickens were divided into 3 groups of body weight, namely high, medium and low.Body size was recorded at 4, 6, 8, 10, and 12 weeks of age, and the weight of flesh and bone at 12 weeks of age was analyzed using the ttest.The samples used to obtain the weight of meat and bones (breast and thighs) were 35 males and 23 females.The study used principal component analysis to identify body size and shape characteristics for males and females. Regression and correlation analysis were then conducted to determine the relationship and closeness between body size and the weight of flesh and bone.The results of the study showed that the body size and weight of flesh and bone in kampung male chickens aged 12 weeks were significantly higher